Penyebab Naiknya Temperatur Fresh Water Pada Generator Di TB. MDM Borneo - S, Amrullah; Radhia M. Mappagiling, Andi; Sularno, Heri; Rusdi, M.; Erlan (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The high temperature that results from combustion in generator can cause damage to both the piston and the cylinder if the cylinder is not cooled. This is because the oil that lubricates the piston will thin and evaporate quickly. As a result, keeping the cooling water's normal temperature requires attention, given the significance of the fresh water cooling system in the onboard generator's operation. The goal of this study is to identify the reason behind the rise in the generator's fresh water temperature, as well as the effects and actions taken to bring it back to normal. The study's data analysis method is descriptive analysis, which describes the data gathered from field studies and literature. It also explains the causes of the rise in the generator's fresh water temperature, which include a lack of cooling water and a drop in fresh water pump pressure from 2 kg/cm² to 1.7 kg/cm². The effect of this increase is that the engine temperature does not match its operating temperature, which leads to excessive heat, or what is known as overheating. To normalize the generator's fresh water temperature, cooling water is added, the fresh water circulation pump's pressure is increased, and the Fresh Water Cooler is cleaned.